Governance of Village-Owned Enterprises-Village Financial Institutions (BUMDesma-LKD) from a Sharia economic perspective: Analysis of institutional readiness - Sujana, I Wayan; Ridzal, Nining Asniar (Journal of Islamic Economics Lariba, 2026)
IntroductionVillage-Owned Enterprises–Village Financial Institutions are expected to strengthen village economic independence, expand financial inclusion, and improve community welfare through the collective management of local resources. However, in Central Buton Regency, these institutions remain dependent on revolving funds, have limited business diversification, and face weaknesses in administration, transparency, financial reporting, and community participation. Sharia economic governance offers an alternative framework based on justice, accountability, transparency, sustainability, and public benefit; however, its implementation depends on adequate institutional readiness.ObjectivesThis study examines the institutional readiness of Village-Owned Enterprises (VOEs) and village financial institutions (VFIs) in Central Buton Regency to implement governance based on a Sharia economic perspective. It also formulates policy recommendations to support gradual, accountable, and sustainable institutional transformation.MethodThis study used a descriptive qualitative design. Primary data were collected through in-depth interviews, focus group discussions, triangulation, and open-ended questionnaires involving managers, supervisors, religious leaders, beneficiaries, local government representatives, and representatives of Islamic financial institutions. Secondary data were obtained from institutional regulations, administrative documents and financial reports. The data were analyzed using thematic analysis supported by qualitative data analysis software and a strengths, weaknesses, opportunities, and threats analysis.ResultsThe findings show that institutional readiness is partial and uneven. Values such as fairness, transparency, deliberation, and concern for beneficiaries are informally present, but formal Sharia governance mechanisms have not been established. Savings and loan activities still use interest-based arrangements, while sharia contracts, standard operating procedures, supervisory structures, and compliance systems are largely absent. Limited managerial knowledge and inadequate community education also prevent stakeholders from distinguishing Sharia-based governance from conventional practices. Nevertheless, strong religious and cultural acceptance and available institutional partnerships create favorable opportunities for transformation.ImplicationsThe transition toward Shariah-based governance requires coordinated reforms in regulation, managerial competence, supervision, financial administration, digitalization, business diversification, and community participation.Originality/NoveltyThis study contributes to the literature by integrating institutional theory with Sharia economic governance and treating Sharia transformation as a multidimensional readiness process rather than merely a change in financing contracts.